Identification of advantages and disadvantages of commercialisation channels in peasant economies in two municipalities from Meta and Cundinamarca, Colombia - López-Posada, Juan Carlos; Pachón-Ariza, Fabio Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
One of the primary functions of the peasant economy is the production of food for self-consumption. This activity is carried out without the detriment of the generation of surpluses to commercialise and thus satisfy other essential needs; in this way, the peasant families organise their production. Given this context, farmers seek for different channels to commercialise their products. For the analysed cases, ( the municipalities of Fuente de Oro, in Meta State, and El Colegio, in Cundinamarca State), the commercialisation of products has been carried out through the program called ‘Mercados Campesinos’ and other alternative channels. Through the methodology ‘Circuito de Mercados Campesinos', an accompaniment to a family from each municipality was made to identify the advantages and disadvantages of the commercialisation channels used by them. The findings show that the marketing in the ‘Mercados Campesinos’ is the favourite one, even though, they continue searching for alternative channels to access other markets. The most significant limitation that was identified during the process was transporting, which makes that peasants look for the middleman to facilitate getting to markets.